Pencak Silat as an extracurricular activity: A literature assessment of its significance in addressing the issues of character education in the 21st century - Jefrio Nubatonis; Salmon Runesi; Ronal Dwi Ardian Fufu; Xander Faldo Ribut Alexander; Muhamad Husein (Journal of Applied Movement and Sport Science, 2026)
Background Education in the 21st century demands a paradigm shift from merely transferring knowledge to shaping individuals who are intellectually, emotionally, and socially competent. Schools are not only places where educational processes occur, but also where learning takes place. However, many schools still focus more on academic achievement than on non-academic values, which often leads to the neglect of character education such as students’ discipline, which is beginning to decline. Objectives This article aims to examine the role of pencak silat as an extracurricular activity in addressing the challenges of 21st-century education through a literature review approach. Methods The research method used in this study is a literature review, which is conducted by collecting, reading, examining, and analyzing various sources of literature relevant to the topic or issue being studied. Results Pencak silat, as a cultural heritage of the nation, holds great potential in character building and the development of students’ soft skills. Based on a review of various literature, it is found that pencak silat not only contributes to physical development but also instills values such as discipline, responsibility, cooperation, and nationalism. This article recommends that pencak silat be optimally utilized as part of a holistic character education strategy. The six articles used as references indicate that pencak silat is not merely a physical activity, but also a form of teaching that can significantly contribute to the development of students’ values and character. Conclusion Based on the review of the six articles above, it can be concluded that Pencak Silat contains elements of character education such as discipline, responsibility, and respect. Regular training in Pencak Silat instills perseverance and a strong fighting spirit. In addition, through social interaction in group training, students learn to cooperate and appreciate differences. Moreover, 21st-century education demands the mastery of soft skills. In Pencak Silat, students are trained to focus, think strategically, and manage their emotions. These values are highly relevant to the demands of today’s workforce and the complexities of social life. As an extracurricular activity, Pencak Silat plays a strategic role in addressing the challenges of 21st-century education. Through a literature-based approach, it is found that Pencak Silat not only supports the development of students’ character and soft skills, but also strengthens the nation's cultural identity.